Intraspecific adaptive radiation: Competition, ecological opportunity, and phenotypic diversification within species. (1st October 2017) - Levis, Nicholas A.; Martin, Ryan A.; O'Donnell, Kerry A.; Pfennig, David W.
Abstract: Intraspecific variation in resource‐use traits can have profound ecological and evolutionary implications. Among the most striking examples are resource polymorphisms, where alternative morphs that utilize different resources evolve within a population. An underappreciated aspect of their evolution is that the same conditions that favor resource polymorphism—competition and ecological opportunity—might foster additional rounds of diversification within already existing morphs. We examined these issues in spadefoot toad tadpoles that develop into either a generalist "omnivore" or a specialist "carnivore" morph. Specifically, we assessed the morphological diversity of tadpoles from natural ponds and experimentally induced carnivores reared on alternative diets. We also surveyed natural ponds to determine if the strength of intramorph competition and the diversity and abundance of dietary resources (measures of ecological opportunity) influenced the diversity of within‐morph variation. We found that five omnivore and four carnivore types were present in natural ponds; alternative diets led to shape differences, some of which mirrored variation in the wild; and both competition and ecological opportunity were associated with enhanced morphological diversity in natural ponds. Such fine‐scale intraspecific variation might represent an underappreciated form of biodiversity and might constitute a crucible of evolutionary innovation and diversification.